2022
DOI: 10.1177/14733250221076061
|View full text |Cite
|
Sign up to set email alerts
|

“Why wasn’t I doing this before?”: Changed school social work practice in response to the COVID-19 pandemic

Abstract: The American education system has been significantly disrupted by the COVID-19 pandemic, which led schools to shut down and convert to remote learning environments in spring 2020. However, long before these school closures, school social workers (SSWs) have faced significant practice dilemmas, as they have encountered obstacles to their engagement in best practices. While initial pandemic school closures presented SSWs with a range of uncertain situations, they also provided the possibility to respond to pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Schools must learn from the needs that their children and families expressed during the period of remote learning, as it is likely that, for many families, these needs are still present even though schools are back in session. Research has demonstrated that school social workers, in the face of the pandemic and the mounting needs of children, families, schools, and communities, were forced to expand their roles and implement universal intervention models [46,55]. Moving forward, it is critical for schools to tailor their support and methods of engagement with families to their contexts and needs [15].…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Schools must learn from the needs that their children and families expressed during the period of remote learning, as it is likely that, for many families, these needs are still present even though schools are back in session. Research has demonstrated that school social workers, in the face of the pandemic and the mounting needs of children, families, schools, and communities, were forced to expand their roles and implement universal intervention models [46,55]. Moving forward, it is critical for schools to tailor their support and methods of engagement with families to their contexts and needs [15].…”
Section: Practice Implicationsmentioning
confidence: 99%